Dosimetric benefits of IMRT and VMAT in the treatment of middle thoracic esophageal cancer: is the conformal radiotherapy still an alternative option?. (8th May 2014) - Wu, Zhiqin; Xie, Congying; Hu, Meilong; Han, Ce; Yi, Jinling; Zhou, Yongqiang; Yan, Huawei; Jin, Xiance
Abstract : The purpose of this study is to investigate the dosimetric differences among conformal radiotherapy (CRT), intensity‐modulated radiotherapy (IMRT), and volumetric‐modulated radiotherapy (VMAT) in the treatment of middle thoracic esophageal cancer, and determine the most appropriate treatment modality. IMRT and one‐arc VMAT plans were generated for eight middle thoracic esophageal cancer patients treated previous with CRT. The planning target volume (PTV) coverage and protections on organs at risk of three planning schemes were compared. All plans have sufficient PTV coverage and no significant differences were observed, except for the conformity and homogeneity. The lung V5, V10, and V13 in CRT were 47.9% ± 6.1%, 36.5% ± 4.6%, and 33.2% ± 4.2%, respectively, which were greatly increased to 78.2% ± 13.7% ( p < 0.01), 80.8% ± 14.9% ( p < 0.01), 48.4% ± 8.2% ( p = 0.05) in IMRT and 58.6% ± 10.5% ( p = 0.03), 67.7% ± 14.0% ( p < 0.01), and 53.0% ± 10.1% ( p < 0.01) in VMAT, respectively. The lung V20 ( p = 0.03) in VMAT and the V30 ( p = 0.04) in IMRT were lower than those in CRT. Both IMRT and VMAT achieved a better protection on heart. However, the volumes of the healthy tissue outside of PTV irradiated by a low dose were higher for IMRT and VMAT. IMRT and VMAT also had a higher MU, optimization time, and delivery time compared to CRT. In conclusion, all CRT, IMRT, and VMAT plans are able to meet the prescription and there is no clear distinction on PTV coverage. IMRT and VMAT can only decrease the volume of lung and heart receiving a high dose, but at a cost of delivering low dose to more volume of lung and normal tissues. CRT is still a feasible option for middle thoracic esophageal cancer radiotherapy, especially for the cost‐effective consideration. PACS numbers: 87.53.Kn, 87.55.x 87.55.D 87.55.dk